A method for preparing a highly efficient heat-resistant and scald-proof paper cup

By bonding the microcapsule phase change material layer, photocatalytic self-cleaning layer and using EVA foam washer on the paper cup, the problem of increasing weight of nested structure paper cups is solved, and the preparation of high-efficiency heat-resistant and scald-resistant paper cups is achieved, and the heat insulation, waterproof and antibacterial properties of the paper cups are improved.

CN119748968APending Publication Date: 2025-04-04HANGZHOU PEOPLE NEW PACKAGING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070979.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing nested structure has complex production process of anti-scalding paper cups, which leads to an increase in the overall weight of the paper cups, making them inconvenient to carry and transport.

Method used

The microcapsule phase change material layer, photocatalytic self-cleaning layer and EVA foam washer are used to improve the heat insulation, waterproofing and antibacterial properties of the paper cup by bonding to the outer and inner walls of the paper cup.

Benefits of technology

It improves the thermal insulation performance of paper cups and reduces heat transfer, making it less likely to burn when it is filled with high-temperature liquid, improves the comfort of use, and reduces the weight of paper cups, making it easy to carry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245688980000101
    Figure BDA0005245688980000101
  • Figure BDA0005245688980000111
    Figure BDA0005245688980000111
Patent Text Reader

Abstract

The present application belongs to the technical field of paper cups, and specifically discloses a method for preparing an efficient heat-resistant and scald-proof paper cup. The method for preparing an efficient heat-resistant and scald-proof paper cup comprises the following steps: a microcapsule phase change material layer and a photocatalytic self-cleaning layer are sequentially bonded to the outer wall of the cup body, an EVA foam gasket is bonded to the bottom of the cup body, and a silicone oil layer is bonded to the inner wall of the cup body to obtain a heat-resistant and scald-proof paper cup; the raw materials of the photocatalytic self-cleaning layer include the following components: 30-40 parts of PET resin, 10-15 parts of nano titanium dioxide, 18-22 parts of composite fiber, 3-5 parts of polyethylene glycol 400, 13-16 parts of modified montmorillonite, and 1-2 parts of antioxidant. The efficient heat-resistant and scald-proof paper cup prepared in the present application has good cooling and heat preservation effects, is light in weight, and is easy to carry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of paper cups, and in particular to a method for preparing a highly efficient heat-resistant and scald-proof paper cup. Background Art

[0002] As a common daily necessity, paper cups have a relatively simple structure and function and are generally only used to hold beverages. As the demand for paper cups gradually increases, the functional requirements for paper cups are also increasing. Among them, when using paper cups to hold hot water, it is necessary to consider the thermal insulation performance of the paper cups. Most ordinary paper cups on the market have simple appearance and performance. When adding hot water, the poor thermal insulation performance makes it inconvenient for users to hold them and they are easily scalded.

[0003] In the prior art, a nested anti-scalding paper cup is usually used. The paper cup is formed by nesting an inner cup body and an outer cup body. The inner cup body is used to hold liquid, and the outer cup body plays a role of heat insulation and protection. A relatively closed space is formed between the inner and outer cup bodies to play a role of heat preservation. However, the production process of the nested anti-scalding paper cup is complicated, and the nested structure may increase the overall weight of the paper cup, which is not convenient to carry and transport. Summary of the invention

[0004] In order to improve the problem that the nested structure of the scald-proof paper cup increases the overall weight of the paper cup and is inconvenient to carry and transport, the present application provides a method for preparing a high-efficiency heat-resistant scald-proof paper cup.

[0005] The present application provides a method for preparing a highly efficient heat-resistant and scald-proof paper cup, which adopts the following technical solution: A method for preparing a high-efficiency heat-resistant and scald-proof paper cup comprises the following steps: sequentially bonding a microcapsule phase change material layer and a photocatalytic self-cleaning layer to the outer wall of the cup body, bonding an EVA foam gasket to the bottom of the cup body, and bonding a silicone oil layer to the inner wall of the cup body to obtain a heat-resistant and scald-proof paper cup; The raw materials of the photocatalytic self-cleaning layer include the following components: 30-40 parts of PET resin, 10-15 parts of nano titanium dioxide, 18-22 parts of composite fiber, 3-5 parts of polyethylene glycol 400, 13-16 parts of modified montmorillonite and 1-2 parts of antioxidant.

[0006] By adopting the above technical solution, the microcapsule phase change material layer is composed of phase change microcapsules, and the phase change microcapsules are bonded to the outer layer of the paper cup. When the temperature of the liquid in the paper cup increases, the microcapsule phase change material absorbs heat and changes from solid to liquid, which plays a cooling role; conversely, when the temperature of the liquid decreases, the microcapsule phase change material releases heat and changes from liquid to solid, which plays a heat preservation role. The microcapsule phase change material layer can increase the thermal insulation performance of the paper cup, reduce heat transfer, make the paper cup not easy to burn when containing high-temperature liquid, and improve the comfort of use.

[0007] The photocatalytic self-cleaning layer can decompose organic pollutants attached to the outer wall of the paper cup, reduce the growth of bacteria and other microorganisms, and thus improve the hygiene of the paper cup. Among the raw materials of the photocatalytic self-cleaning layer, PET resin has good physical properties, chemical stability and processing performance, providing the necessary strength and toughness to ensure that the self-cleaning layer can be firmly attached to the outer wall of the paper cup. Under the irradiation of light, nano-titanium dioxide can trigger a photocatalytic reaction, decomposing water molecules into hydroxyl free radicals and other highly oxidizing substances, which can oxidize and decompose organic matter, bacteria and other pollutants attached to the outer wall of the paper cup, thereby achieving a self-cleaning effect.

[0008] The composite fiber has excellent mechanical properties and chemical stability, which can enhance the overall strength and toughness of the self-cleaning layer, improve the durability and wear resistance of the self-cleaning layer, and at the same time, the composite fiber can also be used as a carrier of nano-titanium dioxide to improve the dispersibility and utilization rate of the photocatalyst. Polyethylene glycol 400 has good solubility and dispersibility, which helps nano-titanium dioxide, modified montmorillonite and composite fiber to be evenly dispersed in PET resin. Modified montmorillonite has extremely high specific surface area and adsorption performance, which can adsorb and fix pollutants to prevent them from spreading and polluting the surrounding environment. As a carrier of photocatalyst, it improves the dispersibility and catalytic efficiency of photocatalyst.

[0009] The antioxidant can prevent the photocatalytic self-cleaning layer from being affected by oxidation and degradation during processing and use, thereby extending the service life of the self-cleaning layer. An EVA foam gasket is bonded to the bottom of the cup body, which plays a good role in cushioning and shock absorption at the bottom of the cup. A silicone oil layer is bonded to the inner wall of the cup body, which can form a waterproof film on the inner wall of the cup body, effectively preventing moisture or other liquids from penetrating into the inner wall of the cup, thereby keeping the cup dry and clean. The prepared paper cup is light and easy to carry.

[0010] Preferably, the method for preparing the composite fiber comprises the following steps: (1) dispersing polyurethane masterbatch in dimethyl sulfoxide, stirring until completely dissolved to obtain polyurethane spinning solution, wet spinning, and drying to obtain polyurethane fibers; (2) dispersing the modified carbon nanofibers in deionized water, stirring for 20-25 min, adding the polyurethane fibers of step (1), stirring at a temperature of 60-65° C. for 1-2 h, filtering, and drying to obtain a mixture; (3) Spraying chitosan solution onto the mixture of step (2), drying, repeating the spraying 2-3 times, drying after each spraying, and crushing to a length of 0.5-0.8 mm to obtain composite fibers.

[0011] By adopting the above technical solution, the polyurethane masterbatch is spun to obtain polyurethane fibers with high strength and wear resistance. The modified carbon nanofibers also have excellent mechanical properties and strength. When mixed with polyurethane fibers, they can be loaded on the surface of polyurethane fibers to improve the mechanical properties of the system. They are subsequently applied to the self-cleaning layer to increase the mechanical strength, heat resistance and barrier properties of the self-cleaning layer.

[0012] Spray chitosan solution on the mixture. The chitosan solution has good film-forming properties and can form a dense film on the surface of the polyurethane fiber to cover the polyurethane fiber and the modified carbon nanofiber, so that the modified carbon nanofiber adheres to the surface of the polyurethane fiber, thereby increasing the mechanical properties, waterproof properties, and antibacterial properties of the polyurethane fiber. The solution is subsequently used in the self-cleaning layer to increase the comprehensive performance of the self-cleaning layer.

[0013] Preferably, the mass ratio of the polyurethane fiber, the modified carbon nanofiber and the chitosan solution is 1:0.3-0.5:0.08-0.09.

[0014] By adopting the above technical solution, the mass ratio of polyurethane fiber, modified carbon nanofiber and chitosan solution is further limited within a certain range, thereby improving the mechanical strength, waterproof performance and barrier properties of polyurethane fiber. Both polyurethane fiber and modified carbon nanofiber have high strength and excellent mechanical properties. Modified carbon nanofiber can be loaded on the surface of polyurethane fiber, significantly improving the tensile strength, burst resistance and tear resistance of polyurethane fiber, making it less likely to deform or break when subjected to external force. Chitosan has good film-forming properties and can form a dense film on the surface of polyurethane fiber, so that modified carbon nanofiber adheres to the surface of polyurethane fiber, improving the comprehensive performance of polyurethane fiber, and subsequently applied to the self-cleaning layer of paper cups, improving the tensile strength, burst resistance and tear resistance of paper cups, making paper cups more durable.

[0015] Preferably, the preparation method of the modified carbon nanofibers comprises the following steps: dispersing the carbon nanofibers in a hydrochloric acid solution, ultrasonicating for 3-4 hours, filtering, washing with water, and drying to obtain pretreated carbon nanotubes; dispersing the pretreated carbon nanotubes in deionized water, adding sodium dodecylbenzene sulfonate, tin oxide and gum arabic, stirring at a temperature of 70-75°C for 1-2 hours, and drying to obtain modified carbon nanofibers.

[0016] By adopting the above technical scheme, the carbon nanofibers are dispersed in a hydrochloric acid solution, and the obtained pretreated carbon nanotubes have better comprehensive properties, improve the wettability of the carbon nanofibers in water, reduce the agglomeration of the carbon nanofibers, and thus make them easier to disperse in water. Sodium dodecylbenzene sulfonate, as a surfactant, helps to evenly disperse the carbon nanofibers in the system, effectively prevents the agglomeration of the carbon nanofibers during the fiber preparation process, and makes the carbon nanofibers evenly distributed in the fibers. Tin oxide can be loaded on the surface of the carbon nanofibers, improve the microstructure of the fiber surface, and improve the wear resistance and tear resistance of the fibers. Tin oxide also has photocatalytic properties, degrading the residues on the surface of the paper cup to keep the paper cup clean and hygienic.

[0017] Gum Arabic has certain antibacterial properties, viscosity, and compatibility. The viscosity of gum Arabic helps the fibers to be tightly bound, so that tin oxide is stably loaded on the surface of carbon nanofibers, thereby enhancing the mechanical stability of the overall fiber. The various components are mixed to improve the mechanical properties, waterproof and barrier properties, and antibacterial properties of carbon nanofibers. The obtained carbon nanofibers are used in paper cups to improve the mechanical properties, waterproof properties, and barrier properties of paper cups, such as tensile strength and toughness.

[0018] Preferably, the preparation method of the modified montmorillonite comprises the following steps: (1) dispersing montmorillonite in deionized water, adding sodium hexametasulfate, stirring for 1-2 hours, settling, decanting the upper suspension, centrifuging, washing, and drying to obtain purified montmorillonite; (2) Dispersing the plant mixture in deionized water, stirring at a temperature of 60-65° C. for 10-15 minutes, adding the purified montmorillonite, metal organic framework material and ethanol in step (1), continuing to stir for 2-3 hours, and drying to obtain modified montmorillonite.

[0019] By adopting the above technical solution, sodium hexametaphosphate is used as a dispersant to fully disperse the montmorillonite particles to form a uniform suspension, and the upper clearer suspension is decanted. The suspension contains more dispersed montmorillonite particles, and is centrifuged to further remove water and fine impurities in the suspension. After centrifugation, the precipitate is washed with deionized water to remove residual dispersant and other impurities, thereby obtaining purified montmorillonite.

[0020] Metal organic framework materials (MOFs) are crystalline porous materials with large specific surface area and network structure, which can be loaded in the structure of purified montmorillonite to improve the mechanical properties and adsorption of purified montmorillonite. The plant mixture has a certain adhesion, which makes the purified montmorillonite and metal organic framework materials (MOFs) adhere tightly. The addition of ethanol helps to improve the dispersibility of montmorillonite and metal organic framework materials (MOFs) and prevent them from agglomerating. The modified montmorillonite obtained has good adsorption and mechanical properties, and is subsequently applied to paper cups to improve the corresponding performance of paper cups.

[0021] Preferably, the mass ratio of the montmorillonite, the plant mixture and the metal organic framework material is 1:0.5-0.7:1-2.

[0022] By adopting the above technical solution, the mass ratio of montmorillonite, plant mixture and metal organic framework material is further limited within a certain range, and the comprehensive performance of montmorillonite is improved. Montmorillonite has excellent mechanical properties and dispersibility. After mixing with plant mixture and MOFs, it can significantly improve the strength of the surface layer of paper cups, including tensile strength, bending strength and wear resistance. The modified montmorillonite has a large interlayer spacing and good thermal stability, which can effectively reduce the dimensional changes of paper cups caused by temperature and humidity changes during use, and improve the dimensional stability of paper cups.

[0023] MOFs have a porous structure and a large specific surface area, which can significantly improve the gas barrier properties of the paper cup surface and reduce the permeability of gases such as oxygen and carbon dioxide. The plant mixture contains natural ingredients with antibacterial activity, which work together with montmorillonite and MOFs to give the paper cup surface excellent antibacterial properties, effectively inhibiting the growth and reproduction of microorganisms such as bacteria and viruses. Metal organic framework materials (MOFs) can be loaded in the structure of purified montmorillonite, and the plant mixture has a certain degree of adhesion, which makes the purified montmorillonite and metal organic framework materials (MOFs) adhere closely, improving the comprehensive performance of the modified montmorillonite.

[0024] Preferably, the preparation method of the plant mixture comprises the following steps: mixing and crushing waste paper, corn stalks and dry straw, dispersing them in deionized water, soaking them for 2-3 hours, filtering to obtain filter residues, adding the filter residues to a sodium hydroxide solution, heating them at a temperature of 80-85°C for 30-35 minutes, washing them with water, dispersing them in deionized water again, adding nano-silicon dioxide, polyvinyl pyrrolidone and β-cyclodextrin, and drying them to obtain a plant mixture.

[0025] By adopting the above technical scheme, waste paper, corn stalks and dry straw are mixed and crushed, the crushed mixture is dispersed in deionized water, the material is softened, and some soluble impurities are removed, and a filter residue is obtained by filtering, wherein the filter residue mainly contains cellulose, hemicellulose, lignin and some undissolved impurities. The filter residue is added to a sodium hydroxide solution, and the sodium hydroxide can destroy the structure of lignin and hemicellulose, so that they are separated from cellulose to obtain cellulose.

[0026] Cellulose is dispersed in deionized water, and nano-silicon dioxide, polyvinyl pyrrolidone and β-cyclodextrin are added. Nano-silicon dioxide has good mechanical strength, and polyvinyl pyrrolidone has good dispersibility and adhesion, so that nano-silicon dioxide and cellulose are better dispersed in the solution to prevent agglomeration and precipitation. β-cyclodextrin improves the solubility and dispersibility of cellulose, making it easier to disperse and use in aqueous solutions. Nano-silicon dioxide can adhere to the surface of cellulose, and polyvinyl pyrrolidone makes cellulose and nano-silicon dioxide adhere tightly. The obtained plant mixture has good adhesion and mechanical properties, which is subsequently applied to modified montmorillonite, so that the various components in the modified montmorillonite are closely adhered, and the corresponding properties of the modified montmorillonite are improved.

[0027] Preferably, in step (1), a binder is used to bond the microcapsule phase change material layer, the binder is acrylic resin, the thickness formed by the binder is 10-15 μm, and the microcapsule phase change material layer is composed of phase change microcapsules and has a thickness of 30-35 μm.

[0028] By adopting the above technical solution, the thickness of the adhesive and the thickness of the microcapsule phase change material layer are further limited, and the obtained protective layers have better comprehensive performance. The acrylic resin has excellent adhesion, good weather resistance and processability, so that the microcapsule phase change material layer is bonded to the surface of the cup body, thereby improving the comprehensive performance of the cup body.

[0029] Preferably, the silicone oil is evenly applied to the inner wall of the paper cup and dried at 130-135°C.

[0030] By adopting the above technical solution, silicone oil has excellent lubricity, oxidation resistance, weather resistance and chemical stability. In paper cup production, silicone oil is often used as a waterproof coating, applied to the inner wall of paper cups to prevent water penetration. Dry at 130-135℃ to ensure that the silicone oil is completely dry and forms a good waterproof layer.

[0031] Preferably, the preparation method of the photocatalytic self-cleaning layer comprises the following steps: mixing PET resin, nano-titanium dioxide, composite fiber, polyethylene glycol 400, modified montmorillonite and antioxidant, melt blending, wire drawing and pelletizing, melt extruding to obtain a thick film, shaping after biaxial stretching, and cutting to obtain a photocatalytic self-cleaning layer.

[0032] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing high-efficiency heat-resistant and scalding-proof paper cups. The obtained high-efficiency heat-resistant and scalding-proof paper cups have comprehensive properties such as good mechanical properties and stability.

[0033] In summary, this application has the following beneficial effects: 1. In the present application, the microcapsule phase change material layer is composed of phase change microcapsules, and the phase change microcapsules are bonded to the outer layer of the paper cup. When the temperature of the liquid in the paper cup rises, the microcapsule phase change material absorbs heat and changes from solid to liquid, which has a cooling effect; conversely, when the temperature of the liquid decreases, the microcapsule phase change material releases heat and changes from liquid to solid, which has a heat preservation effect.

[0034] 2. The photocatalytic self-cleaning layer in the present application can decompose organic pollutants attached to the outer wall of the paper cup, reduce the growth of bacteria and other microorganisms, and thus improve the hygiene of the paper cup; a silicone oil layer is bonded to the inner wall of the cup body, and the silicone oil layer can form a waterproof film on the inner wall of the cup body, effectively preventing moisture or other liquids from penetrating into the inside of the cup wall, thereby keeping the cup dry and clean. The prepared paper cup is light and easy to carry.

[0035] 3. In the present application, nano titanium dioxide can trigger a photocatalytic reaction under the irradiation of light, decomposing water molecules into hydroxyl free radicals and other highly oxidizing substances, which can oxidize and decompose pollutants such as organic matter and bacteria attached to the outer wall of the paper cup, thereby achieving a self-cleaning effect. DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the embodiments.

[0037] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0038] Preparation example of composite fiber Preparation Example 1-1 The preparation method of the composite fiber comprises the following steps: (1) dispersing 50 kg of polyurethane masterbatch in 500 L of dimethyl sulfoxide and stirring until completely dissolved to obtain a polyurethane spinning solution; adding 100 kg of ethanol to 300 kg of water and stirring at 35° C. for 1 hour to obtain an ethanol / water mixed solution as a mixed coagulation bath (i.e., as a non-solvent for the mixed coagulation bath); wet spinning and drying to obtain polyurethane fibers; (2) dispersing the modified carbon nanofibers in 100 kg of deionized water, stirring for 25 min, adding the polyurethane fibers of step (1), stirring at a temperature of 65° C. for 2 h, filtering, and drying to obtain a mixture; (3) Spraying chitosan solution onto the mixture of step (2), drying, repeating the spraying for 3 times, drying after each spraying, and crushing to a length of 0.5-0.8 mm to obtain composite fibers.

[0039] The diameter of the wet spinning head was 300 μm, the injection speed was 5 mL / min, and the collection rate was 60 m / min.

[0040] Chitosan was dispersed in 30 L of 10% by mass acetic acid solution and stirred evenly to obtain a chitosan solution.

[0041] The mass ratio of polyurethane fiber, modified carbon nanofiber and chitosan solution is 1:0.3:0.09.

[0042] The preparation method of modified carbon nanofibers comprises the following steps: dispersing 40 kg of carbon nanofibers in 80 L of hydrochloric acid solution with a mass fraction of 30%, ultrasonically treating for 4 hours, filtering, washing with water, and drying to obtain pretreated carbon nanotubes; dispersing the pretreated carbon nanotubes in 90 L of deionized water, adding 2 kg of sodium dodecylbenzene sulfonate, 8 kg of tin oxide, and 5 kg of gum arabic, stirring at a temperature of 75° C. for 2 hours, and drying to obtain modified carbon nanofibers.

[0043] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified carbon nanofibers are added.

[0044] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no chitosan solution is added.

[0045] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of the polyurethane fiber, the modified carbon nanofiber and the chitosan solution is 1:0.5:0.08.

[0046] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of the polyurethane fiber, the modified carbon nanofiber and the chitosan solution is 1:0.1:0.15.

[0047] Preparation Example 1-6 The difference from Preparation Example 1-1 is that tin oxide is not added in the preparation method of the modified carbon nanofibers.

[0048] Preparation Example 1-7 The difference from Preparation Example 1-1 is that gum arabic is not added in the preparation method of the modified carbon nanofibers.

[0049] Preparation example of modified montmorillonite Preparation Example 2-1 The preparation method of modified montmorillonite comprises the following steps: (1) Dispersing 100 kg of montmorillonite in 350 L of deionized water, adding 20 kg of sodium hexametasulfate, stirring for 2 h, settling, decanting the upper suspension, centrifuging, washing, and drying to obtain purified montmorillonite; (2) The plant mixture was dispersed in 100 L of deionized water, stirred at 65°C for 15 min, the purified montmorillonite, metal organic framework material (MOFs) and 20 L of ethanol from step (1) were added, the stirring was continued for 3 h, and the mixture was dried to obtain modified montmorillonite. The metal organic framework material (MOFs) was purchased from Suzhou Kaifa New Materials Technology Co., Ltd.

[0050] The mass ratio of montmorillonite, plant mixture and metal-organic framework material is 1:0.5:2.

[0051] The preparation method of a plant mixture comprises the following steps: mixing and crushing 70 kg of waste paper, 50 kg of corn stalks and 30 kg of dry rice straw, dispersing the mixture in 300 L of deionized water, soaking the mixture for 3 hours, filtering the mixture to obtain a filter residue, adding the filter residue to 200 L of a sodium hydroxide solution with a mass fraction of 10%, heating the mixture at a temperature of 85°C for 35 minutes, washing the mixture with water, dispersing the mixture in 300 L of deionized water, adding 20 kg of nano silicon dioxide, 10 kg of polyvinyl pyrrolidone and 15 kg of beta-cyclodextrin, and drying the mixture to obtain a plant mixture.

[0052] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no plant mixture is added.

[0053] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), no metal organic framework material (MOFs) is added.

[0054] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of montmorillonite, plant mixture and metal organic framework material is 1:0.7:1.

[0055] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of montmorillonite, plant mixture and metal organic framework material is 1:0.1:5.

[0056] Preparation Example 2-6 The difference from Preparation Example 2-1 is that no nano-silicon dioxide is added in the preparation method of the plant mixture.

[0057] Preparation Example 2-7 The difference from Preparation Example 2-1 is that β-cyclodextrin is not added in the preparation method of the plant mixture. Example

[0058] Example 1 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, comprising sequentially bonding a microcapsule phase change material layer and a photocatalytic self-cleaning layer to the outer wall of the cup body, bonding an EVA foam gasket to the bottom of the cup body, and bonding a silicone oil layer to the inner wall of the cup body to obtain a heat-resistant and scald-proof paper cup; The raw materials of the photocatalytic self-cleaning layer include the following components: 30kg of PET resin, 10kg of nano titanium dioxide, 18kg of composite fiber, 3kg of polyethylene glycol 400, 13kg of modified montmorillonite and 1kg of antioxidant.

[0059] The microcapsule phase change material layer is bonded with an adhesive, the adhesive is acrylic resin, and the thickness formed by the adhesive is 13 μm. The microcapsule phase change material layer is composed of phase change microcapsules and has a thickness of 32 μm. The photocatalytic self-cleaning layer has a thickness of 35 μm and the silicone oil layer has a thickness of 8 μm.

[0060] Phase change microcapsules were purchased from Anhui Meikedi Intelligent Microcapsule Technology Co., Ltd. The phase change temperature was 37°C, and the phase change microcapsules were evenly coated on the outer wall of the cup.

[0061] The silicone oil is evenly applied on the inner wall of the paper cup and dried at 130-135℃.

[0062] The EVA foam gasket was bonded with an adhesive, and the thickness of the adhesive was 7 μm. The EVA foam gasket was purchased from Shouxinren Plastic Packaging Factory, Shunde District, Foshan City, and was cut into a circle with a diameter the same as the bottom diameter of the cup body and a thickness of 1 mm.

[0063] The preparation method of the photocatalytic self-cleaning layer comprises the following steps: mixing PET resin, nano titanium dioxide, composite fiber, polyethylene glycol 400, modified montmorillonite and antioxidant, melt blending, wire drawing and pelletizing, melt extruding to obtain a thick film, shaping after biaxial stretching, cutting and obtaining the photocatalytic self-cleaning layer.

[0064] Melt extrusion step: the raw material mixture is sent into a twin-screw extruder for melt extrusion, and the extruder temperature is set to: 190℃-210℃-230℃-250℃-260℃-280℃ to form a molten film, and then the film molten film is cast on a cooling roller through a casting die for quenching to form a cast sheet. The cooled cast sheet is placed in a stretching machine, and the longitudinal stretching is to preheat the cast sheet to 95℃, and longitudinally stretch it 3.5 times at this temperature, the transverse stretching preheating temperature is 98℃, the stretching temperature is 120℃, the stretching ratio is 4.5 times, and the film is biaxially stretched by the stretching machine to form a film. The stretched film is placed in a setting machine, and the film passes through a hot roller for hot pressing and setting. The film after hot pressing and setting passes through a cooling roller, and the film is cooled and set to obtain a photocatalytic self-cleaning layer.

[0065] The composite fiber was prepared by using Preparation Example 1-1; the modified montmorillonite was prepared by using Preparation Example 2-1.

[0066] Example 2 A method for preparing an efficient heat-resistant and scald-proof paper cup, which is different from Example 1 in that the raw materials of the photocatalytic self-cleaning layer include the following components: 40 kg of PET resin, 15 kg of nano titanium dioxide, 22 kg of composite fiber, 5 kg of polyethylene glycol 400, 16 kg of modified montmorillonite, and 2 kg of antioxidant.

[0067] Example 3 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the composite fiber is prepared using Preparation Example 1-2.

[0068] Example 4 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the composite fiber is prepared using Preparation Examples 1-3.

[0069] Example 5 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the composite fiber is prepared using Preparation Examples 1-4.

[0070] Example 6 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the composite fiber is prepared using Preparation Examples 1-5.

[0071] Example 7 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the composite fiber is prepared using Preparation Examples 1-6.

[0072] Example 8 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the composite fiber is prepared using Preparation Examples 1-7.

[0073] Example 9 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Example 2-2.

[0074] Example 10 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Example 2-3.

[0075] Embodiment 11 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Examples 2-4.

[0076] Example 12 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Examples 2-5.

[0077] Embodiment 13 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Examples 2-6.

[0078] Embodiment 14 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the modified montmorillonite is prepared using Preparation Examples 2-7.

[0079] Comparative Example Comparative Example 1 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which differs from Example 1 in that no composite fiber is added.

[0080] Comparative Example 2 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which is different from Example 1 in that the composite fiber is purchased from Shandong Hongyao Copper Materials Co., Ltd.

[0081] Comparative Example 3 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which differs from Example 1 in that modified montmorillonite is not added.

[0082] Comparative Example 4 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which differs from Example 1 in that the modified montmorillonite is replaced by an equal amount of montmorillonite.

[0083] Comparative Example 5 A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, which differs from Example 1 in that no microcapsule phase change material layer is added.

[0084] Performance testing The high-efficiency heat-resistant and scald-proof paper cups prepared in Examples 1-14 and Comparative Examples 1-4 were subjected to performance tests. The temperature of the outer wall of the paper cup was tested by an infrared thermometer to characterize the heat insulation effect of the paper cup. Hot water at 100° C. was added to the paper cup to test the temperature of the outer wall of the paper cup. The stiffness and bursting index of paper cups refer to GB / T 27590-2011, the tensile index and folding endurance of paper cups refer to GB / T 12914, the folding endurance of paper cups refer to GB2679.5 "Determination of folding endurance of paper and paperboard", and the tear index of paper cups refer to GB / T 455.1-2008 "Determination of tear resistance of paper and paperboard Part 1: Elmendorf method". The test results are shown in Table 1.

[0085] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the high-efficiency heat-resistant and scald-proof paper cups prepared in Examples 1-2 of the present application have good mechanical properties and thermal insulation properties. Among them, the temperature of the outer wall of the paper cup of Example 1 is 70°C, the tensile index is 92.85N﹒ m / g, the folding endurance is 198 times, and the bursting index is 9.1kPa﹒ m 2 / g, tear index is 15.62mN﹒ m 2 / g, and the stiffness is 9986mN. In Comparative Example 5, no microcapsule phase change material layer is added, and the temperature of the outer wall of the paper cup is 90°C, indicating that the prepared high-efficiency heat-resistant and scalding-proof paper cup is composed of phase change microcapsules, so that the paper cup is not easy to burn when containing high-temperature liquids, and the photocatalytic self-cleaning layer can decompose organic pollutants attached to the outer wall of the paper cup, reduce the growth of bacteria and other microorganisms, and also has good strength and toughness, thereby improving the durability of the paper cup.

[0086] In the preparation method of the composite fiber of Examples 3-4, modified carbon nanofibers and chitosan solution are not added respectively, and the mass ratio of polyurethane fiber, modified carbon nanofiber and chitosan solution is changed in Examples 5-6. It can be seen from Table 1 that the test results of tensile index, folding endurance, burst index, tear index and stiffness of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the corresponding performance test of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1-2 and Example 5, indicating that chitosan has good film-forming properties and can form a dense film on the surface of polyurethane fibers, so that the modified carbon nanofibers adhere to the surface of polyurethane fibers, improve the comprehensive performance of polyurethane fibers, and are subsequently applied to the self-cleaning layer of paper cups to improve the tensile strength, burst resistance and tear resistance of paper cups, making paper cups more durable.

[0087] In the preparation method of the modified carbon nanofibers of Examples 7-8, tin oxide and gum arabic are not added respectively. As can be seen from Table 1, the test results of the tensile index, folding endurance, burst index, tear index and stiffness of Examples 7-8 are significantly better than those of Example 3, but worse than those of Examples 1-2 and Example 5, indicating that the viscosity of gum arabic contributes to the close bonding between fibers, so that tin oxide is stably loaded on the surface of the carbon nanofibers, thereby enhancing the mechanical stability of the overall fiber. It is applied to paper cups to improve the mechanical properties such as tensile strength and toughness, waterproof properties, and barrier properties of the paper cups.

[0088] In the preparation method of modified montmorillonite in Examples 9-10, plant mixture and metal organic framework material (MOFs) are not added respectively. In Examples 11-12, the mass ratio of montmorillonite, plant mixture and metal organic framework material is changed. It can be seen from Table 1 that the test results of tensile index, folding endurance, bursting index, tear index and stiffness of Examples 9-10 are significantly worse than those of Examples 1-2 and Example 11, while the corresponding performance test of Example 12 is better than that of Examples 9-10, but worse than that of Examples 1-2 and Example 11, indicating that metal organic framework material (MOFs) can be loaded in the structure of purified montmorillonite, and the plant mixture has a certain adhesion, so that the purified montmorillonite and metal organic framework material (MOFs) are closely bonded, thereby improving the comprehensive performance of the modified montmorillonite, thereby improving the corresponding performance of the paper cup.

[0089] In the preparation method of the plant mixture of Examples 13-14, nano silicon dioxide and β-cyclodextrin are not added respectively. As can be seen from Table 1, the test results of the tensile index, folding endurance, bursting index, tear index and stiffness of Examples 13-14 are significantly better than those of Example 9, but worse than those of Examples 1-2 and Example 11, indicating that β-cyclodextrin improves the solubility and dispersibility of cellulose, making it easier to disperse and use in aqueous solutions, nano silicon dioxide can adhere to the surface of cellulose, and polyvinyl pyrrolidone makes cellulose and nano silicon dioxide bond tightly. The obtained plant mixture has good adhesion and mechanical properties, and is subsequently applied to modified montmorillonite, so that the components in the modified montmorillonite are tightly bonded, thereby improving the corresponding properties of the modified montmorillonite, and then improving the corresponding properties of the paper cup.

[0090] In Comparative Examples 1 and 3, no composite fiber and modified montmorillonite are added, respectively. As can be seen from Table 1, the test results of tensile index, folding endurance, bursting index, tear index and stiffness of Comparative Examples 1 and 3 are significantly worse than those of Examples 1-2, indicating that the composite fiber and modified montmorillonite have excellent mechanical properties, thereby improving the comprehensive performance of the paper cup.

[0091] In Comparative Examples 2 and 4, the composite fibers are commercially available and the modified montmorillonite is replaced by an equal amount of montmorillonite. As can be seen from Table 1, the test results of the tensile index, folding endurance, bursting index, tear index and stiffness of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified composite fibers and modified montmorillonite of the present application have better mechanical properties, thereby improving the mechanical properties of the paper cup and maintaining the durability and stability of the paper cup.

[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a high-efficiency heat-resistant and scald-proof paper cup, characterized in that: The method comprises the following steps: sequentially bonding a microcapsule phase change material layer and a photocatalytic self-cleaning layer to the outer wall of the cup body, bonding an EVA foam gasket to the bottom of the cup body, and bonding a silicone oil layer to the inner wall of the cup body to obtain a heat-resistant and scald-proof paper cup; The raw materials of the photocatalytic self-cleaning layer include the following components: 30-40 parts of PET resin, 10-15 parts of nano titanium dioxide, 18-22 parts of composite fiber, 3-5 parts of polyethylene glycol 400, 13-16 parts of modified montmorillonite and 1-2 parts of antioxidant.

2. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 1, characterized in that: The preparation method of the composite fiber comprises the following steps: (1) dispersing the polyurethane masterbatch in dimethyl sulfoxide, stirring until completely dissolved to obtain a polyurethane spinning solution, wet spinning, and drying to obtain a polyurethane fiber; (2) dispersing the modified carbon nanofibers in deionized water, stirring for 20-25 minutes, adding the polyurethane fibers of step (1), stirring at a temperature of 60-65° C. for 1-2 hours, filtering, and drying to obtain a mixture; (3) Spraying chitosan solution onto the mixture of step (2), drying, repeating the spraying 2-3 times, drying after each spraying, and crushing to a length of 0.5-0.8 mm to obtain composite fibers.

3. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 2, characterized in that: The mass ratio of the polyurethane fiber, the modified carbon nanofiber and the chitosan solution is 1:0.3-0.5:0.08-0.

09.

4. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 2, characterized in that: The preparation method of the modified carbon nanofibers comprises the following steps: dispersing the carbon nanofibers in a hydrochloric acid solution, ultrasonicating for 3-4 hours, filtering, washing with water, and drying to obtain pretreated carbon nanotubes; The pretreated carbon nanotubes are dispersed in deionized water, sodium dodecylbenzene sulfonate, tin oxide and gum arabic are added, stirred at a temperature of 70-75° C. for 1-2 hours, and dried to obtain modified carbon nanofibers.

5. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 1, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: (1) Dispersing montmorillonite in deionized water, adding sodium hexametasulfate, stirring for 1-2 hours, settling, decanting the upper suspension, centrifuging, washing, and drying to obtain purified montmorillonite; (2) Dispersing the plant mixture in deionized water, stirring at a temperature of 60-65° C. for 10-15 minutes, adding the purified montmorillonite, metal organic framework material and ethanol from step (1), continuing to stir for 2-3 hours, and drying to obtain modified montmorillonite.

6. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 5, characterized in that: The mass ratio of the montmorillonite, the plant mixture and the metal organic framework material is 1:0.5-0.7:1-2.

7. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 5, characterized in that: The preparation method of the plant mixture comprises the following steps: mixing and crushing waste paper, corn stalks and dry straw, dispersing them in deionized water, soaking them for 2-3 hours, filtering to obtain filter residues, adding the filter residues into a sodium hydroxide solution, heating them at a temperature of 80-85°C for 30-35 minutes, washing them with water, dispersing them in deionized water again, adding nano silicon dioxide, polyvinyl pyrrolidone and beta-cyclodextrin, and drying them to obtain the plant mixture.

8. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 1, characterized in that: In step (1), a binder is used to bond the microcapsule phase change material layer. The binder is an acrylic resin. The thickness formed by the binder is 10-15 μm. The microcapsule phase change material layer is composed of phase change microcapsules and has a thickness of 30-35 μm.

9. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 1, characterized in that: The silicone oil is evenly applied on the inner wall of the paper cup and dried at 130-135°C.

10. The method for preparing a high-efficiency heat-resistant and scald-proof paper cup according to claim 1, characterized in that: The preparation method of the photocatalytic self-cleaning layer comprises the following steps: mixing PET resin, nano titanium dioxide, composite fiber, polyethylene glycol 400, modified montmorillonite and antioxidant, melt blending, wire drawing and pelletizing, melt extruding to obtain a thick film, biaxially stretching and then shaping, cutting to obtain the photocatalytic self-cleaning layer.